Ornamentyka figuralna na naczyniach glinianych okresu przedrzymskiego i rzymskiego w Polsce - Bugaj, Ewa; Makiewicz, Tadeusz (My University, 1995)
The article discusses figural ornamentation in clay vessels dated to pre-Roman and Roman periods found on territory of Poland. A catalogue description, structural and typological analysis, and determining chronology and the function of the objects made it possible to place this group in the cultural background of analogous findings of Celtic and Germanic prehistoric societies ceramics from the Barbaricum area and Great Britain. Figural motifs show remarkable variety in images and the techniques employed, since they occur in board chronological frames.
Keywords: Figurative Decoration of Pottery; pre-Roman and Roman Middle Europe